2022
DOI: 10.1111/and.14611
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tobacco smoking in association with H2BFWT , PRM1 and PRM2 genes variants on male infertility

Abstract: Tobacco's genotoxic components can cause a wide range of gene defects in spermatozoa such as single-or double-strand DNA breaks, cross-links, DNA-adducts, higher frequencies of aneuploidy and chromosomal abnormalities. The aim in this study was to determine the correlation between sperm quality determined by standard parameters, sperm DNA maturity tested by Chromomycin A3 (CMA3) staining, sperm DNA fragmentation tested by TUNEL assay and tobacco smoking in association with the single nucleotides polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
(71 reference statements)
2
5
0
Order By: Relevance
“…This study confirms that cigarette smoke plays a crucial role in altering human gene transcription levels in sperm as it affects chromatin remodeling [15], and global DNA methylation status [54], and DNA methylation at different CpG sites [8].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This study confirms that cigarette smoke plays a crucial role in altering human gene transcription levels in sperm as it affects chromatin remodeling [15], and global DNA methylation status [54], and DNA methylation at different CpG sites [8].…”
Section: Discussionsupporting
confidence: 76%
“…Several other factors, including age, stress, and lifestyle, such as obesity, smoking, and alcohol use, have been linked to male infertility [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Amor et al (2022) found no significant difference in allele frequency between heavy smokers and non-smokers for 3 homozygous SNPs in H2BFWT. Furthermore, the identified SNPs had no effect on sperm parameters and its DNA integrity [52].…”
Section: Introductionmentioning
confidence: 91%
“…Additionally, gene variations induced by smoking and exposure to toxic polycyclic aromatic hydrocarbons present in cigarettes may play a role. [99][100][101] Overall, these studies emphasize the importance of quitting or reducing cigarette smoking to prevent higher SDF levels, which could have a significant impact on fertility and overall reproductive health.…”
Section: Lifestyle Changesmentioning
confidence: 98%